Question

Sol. We have the equations:
( frac{15}{x}+frac{2}{y}=17 )
and
[
frac{1}{x}+frac{1}{y}=frac{36}{5}
]
( frac{2}{x}+frac{2}{y}=frac{72}{5} )
11
Multiplying eq.
(ii) by ( 2, ) we get,
Subtracting (iii) from (i), we get
[
begin{array}{l}
frac{15}{x}-frac{2}{y}=17-frac{72}{5} Rightarrow frac{13}{x}=frac{85-72}{5} Rightarrow frac{13}{x}=frac{13}{5}
Rightarrow quad x times 13=13 times 5 quad Rightarrow x=frac{13 times 5}{13}=5
end{array}
]
Putting the value of ( x ) in (ii), we get
[
frac{1}{5}+frac{1}{y}=frac{36}{5} Rightarrow frac{1}{y}=frac{36}{5}-frac{1}{5} Rightarrow frac{1}{y}=frac{35}{5} Rightarrow 35 times y=5 Rightarrow y=frac{5}{35} quad therefore quad y=frac{1}{7}
]
Hence, ( x=5, y=frac{1}{7} )

# 15 2 1 1 36 Solve : — + = = 17, -+-- = — хух у 5

Solution